EVALUASI INTERAKSI OBAT JANTUNG KORONER PADA PASIEN RAWAT INAP DI RUMAH SAKIT UMUM IMELDA PEKERJA INDONESIA MEDAN - Auliafendri, Novycha; Darmiyani (JIFI (Jurnal Ilmiah Farmasi Imelda), 2022)
Coronary heart disease is the most common cause of death globally. Deaths in patients with coronary heart disease are 7.8 million out of 11.11 million people in developing countries in 2020. One of the factors that can worsen heart disease is drug interactions caused by patients with heart disease not only having one disease but followed by other diseases. so that they use more than one kind of drug. The purpose of this study was to describe the treatment profile of CHD patients and drug interactions in coronary heart inpatients at Imelda General Hospital, Indonesian Workers. This research is an observational study designed with retrospective descriptive design. Data analysis was carried out by screening drug interactions using the Drug Interaction Checker. The results showed that the criteria for CHD patients mostly occurred in women (56.3%) at the age of 56-60 years (23.9%). The distribution of diagnoses in CHD patients had the most three diagnoses of disease and with the most comorbidities, namely dyspepsia (20.6%) and diabetes mellitus (19.0%). The most widely used coronary heart therapy in inpatients at Imelda Workers' Hospital in Indonesia was SDN (12.7%) while the combination therapy was Clopidogrel and Concor (4.2%). Drug interactions in CHD patients were mostly nifedipine and atorvastatin with moderate levels.